2023
DOI: 10.3390/gidisord5040036
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and Public Interest in Bariatric Surgery for Obesity: The Italian Scenario

Chiara Mazzone,
Salvatore Pezzino,
Maria Sofia
et al.

Abstract: Background: Obesity is an escalating concern in our society. Bariatric surgery appears to be the only feasible alternative for severe obesity. This study aims to conduct an integrative analysis of the Italian context concerning bariatric surgery, with a specific focus on the surgical procedures of sleeve gastrectomy, mini-gastric bypass, and gastric bypass. Methods: The analysis is based on bibliometric data extracted from the Scopus database to find Italian publications in this field from 2012 to 2022. Along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Sleeve gastrectomy (SG) is a commonly used form of bariatric surgery that primarily restricts the size of the stomach [293,294]. This procedure involves the removal of a substantial amount of the stomach, including its modest curvature, resulting in the formation of a sleeve-shaped stomach [293].…”
Section: Ghrelinmentioning
confidence: 99%
“…Sleeve gastrectomy (SG) is a commonly used form of bariatric surgery that primarily restricts the size of the stomach [293,294]. This procedure involves the removal of a substantial amount of the stomach, including its modest curvature, resulting in the formation of a sleeve-shaped stomach [293].…”
Section: Ghrelinmentioning
confidence: 99%
“…Electronic data is utilized in this field to monitor online interest in health problems and procedures, predict disease outbreaks, and assess the efficacy of health education efforts 31 . For example, in a recent study, Mikoła et al showed how interest in probiotic-related information may be correlated with antibiotic consumption, health expenditures, and the country's level of development 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%